PEMBELAJARAN MEMBACA LANJUTAN DI SEKOLAH DASAR - Ramadani, Nita; Hamzah, Rahma Ashari; Musyawir, Musyawir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Reading learning in Elementary Schools is an important foundation in developing students' literacy skills. Through reading skills, students are not only able to recognize letters and words, but also understand the contents of the reading as a whole. This study aims to examine strategies, types, and challenges in reading learning, especially advanced reading at the elementary level. The method used is a literature study by analyzing various academic sources such as books, scientific journals, research articles, and education policy documents. The results of the study show that students' reading skills still face various obstacles, especially in terms of reading comprehension and reading speed. The low variety of teaching methods and the lack of interesting learning media are also inhibiting factors. Therefore, innovation is needed in learning approaches that can increase students' motivation and literacy skills in a sustainable manner. This study is expected to be a reference for developing more effective and enjoyable reading learning practices in Elementary Schools.